Tissue inhomogeneity corrections in low-kV intra-operative radiotherapy (IORT) - Sethi, Anil; Chinsky, Bonnie; Gros, Sebastien; Diak, Abbie; Emami, Bahman; Small Jr, William (Translational Cancer Research, 2015)
Objective: To investigate the effects of tissue inhomogeneities on dose distributions produced by low-energy X-rays from an IntraBeam device used in intra-operative radiotherapy (IORT). Methods and materials: A 50 kV IntraBeam X-ray device with superficial (Flat and Surface) applicators has been recently commissioned at the Loyola University Medical Center in Maywood, Illinois (USA). For each applicator type, treatment dose parameters, such as, percent depth-dose (PDD) and output factors (OF) were obtained. Calibrated Gafchromic (EBT3) films (dose range, 0 to 4 Gy) were employed to obtain dose distributions in a solid water phantom at various depths (2, 5, 10, and 15 mm). All recommended precautions with respect to film-handling, film-exposure and scanning were observed. The effect of tissue inhomogeneities on dose distributions was examined by placing air-cavities and bone and tissue equivalent materials with different density (ρ), atomic number (Z), and thickness (t=0-4 mm) between the applicator and film detector. All inhomogeneities were cylindrical with a 25 mm diameter. Treatment time was calculated to deliver 1 Gy dose at 5 mm depth in a homogenous phantom. Film results were verified by repeat measurements with a thin-window parallel plate ion-chamber (PTW 34013A) placed in a water tank. Results: For a flat-4 cm applicator, the dose rate at 5 mm depth in solid water was measured to be 0.349 Gy/min. Introduction of a cylindrical air cavity resulted in an increased dose past the heterogeneity. Compared to dose in a homogenous tissue equivalent medium, dose enhancement due to 1, 2, 3, and 4 mm air cavities was found to be 10%, 16%, 24%, and 35% respectively. X-ray attenuation due to a 2 mm thick layer of cortical bone resulted in a significantly large dose decrease (58%) compared to homogenous conditions. Conclusions: IORT dose calculations assume a homogeneous tissue equivalent medium. However, the treatment conditions may involve the presence of various tissue inhomogeneities, thereby compromising delivered dose. We have investigated the effect of different density materials on dose distributions in IORT. The results of this study may be used to estimate and correct IORT dose delivered in the presence of tissue inhomogeneities.